ORGANIZATIONAL PERFORMANCE AND ELECTRONIC PROCUREMENT - ADRIKO HAROLD (Uganda Christian University, 2024)
This paper examines the relationship between organizational performance and electronic procurement and focuses on Roofings Uganda Limited as a case study. The study is anchored on the Technology Acceptance Model theory and the Resource-Based View theory which provide a framework for fully understanding how organizational performance influences e-procurement practices. The study deployed a quantitative approach in measuring variables using statistical procedures. The sample size will be 50 respondents from different departments at Roofing’s Uganda Ltd, including suppliers, finance, stores, management, production, procurement, human resources and contract. The sample size was 50 respondents from different departments at Roofing’s Uganda Ltd, including suppliers, finance, stores, management, production, procurement, human resources and contract.
The study was about the role of Electronic procurement that improves the organizational performance at Roofings Uganda limited.